Os interesses culturais do lazer nas aulas de Educação Física escolar: uma proposta de unidade didática para o ensino fundamental - Coutinho Netto, João Batista (Universidade Federal de São Carlos, 2024)
Considering the relevance of the leisure theme highlighted by the accumulation of studies in this area, as well as the importance that the subject can assume, through its values and cultural content in the interface with the school environment and also in line with the current debate about the guarantee of constitutional access rights to experiences in this area, this research aimed to investigate the pedagogical potentialities of the application of a Didactic Unit, consisting of 10 classes, on the Cultural Interests of Leisure in School Physical Education classes. The qualitative approach, through the methodology of action research, was carried out with the 18 students of a 5th grade class of Elementary School, in a municipal school in the interior of São Paulo. Field notes served as a data collection instrument and the subsequent data analysis occurred through content analysis. The research efforts revealed two categories: A) Urgency of an education for leisure; B) Leisure in school and leisure of the school. The results pointed out the potential of leisure as a Physical Education theme, notwithstanding the current curricular limitation about spaces, times, and pedagogical actions aimed at experiences in this area in the school environment; it also expressed the deficient student conceptions about the phenomenon of leisure, as well as the legal possibilities of experiences in this context. From the analyses reached, we consider that a school education that intends to employ leisure - in the aspect of cultural interests - as a means and finality of its processes, will update the formation of human beings aware of their rights and prepared to assume their duties towards themselves and in the face of their social responsibilities. We reaffirm school leisure, according to a perspective of its own aimed at this environment, not as an unreflective reproduction of consumer leisure, but rather emancipatory, finding in Physical Education classes a privileged space for development, although it should be explored in other disciplines and in direct actions of school management. We also reinforce our understanding that leisure, given its transversal characteristic, which permeates various contents of Physical Education, gathers qualities to assume the condition of central theme, as an example of games, sports, fights etc., in the scope of School Physical Education, appearing in curricular documents, such as the Brazilian Commom Core , as a unit of knowledge, from which skills and contents can be developed and offered to students, aiming at an education for leisure, through education by leisure.

Considerando la relevancia del tema del ocio destacado por la acumulación de estudios en esta área, así como la importancia que el tema puede asumir, a través de sus valores y contenidos culturales en la interfaz con el entorno escolar y también en línea con el debate actual sobre la garantía de derechos de acceso constitucionales a experiencias en esta área, esta investigación tuvo como objetivo investigar las potencialidades pedagógicas de la aplicación de una Unidad Didáctica, compuesta por 10 clases, sobre los Intereses Culturales del Ocio en las clases de Educación Física Escolar. El enfoque cualitativo, a través de la metodología de la investigación-acción, se llevó a cabo con los 18 estudiantes de una clase de 5º grado de la Escuela Primaria, en una escuela municipal en el interior de São Paulo. Las notas de campo sirvieron como instrumento de recolección de datos y el posterior análisis de datos ocurrió a través del análisis de contenido. Los esfuerzos de investigación revelaron dos categorías: A) Urgencia de una educación para el ocio; B) Ocio en la escuela y ocio de la escolar. Los resultados señalaron el potencial del ocio como tema de Educación Física, a pesar de la limitación curricular actual sobre espacios, tiempos y acciones pedagógicas dirigidas a experiencias en esta área en el entorno escolar; también expresó las deficientes concepciones estudiantiles sobre el fenómeno del ocio, así como las posibilidades legales de experiencias en este contexto. A partir de los análisis alcanzados, consideramos que una educación escolar que pretende emplear el ocio - en el aspecto de los intereses culturales - como medio y fin de sus procesos, actualizará la formación de seres humanos conscientes de sus derechos y preparados para asumir sus deberes hacia sí mismos y ante sus responsabilidades sociales. Reafirmamos el ocio escolar, según una perspectiva propia dirigida a este entorno, no como una reproducción irreflexiva del ocio de consumo, sino más bien emancipadora, encontrando en las clases de Educación Física un espacio privilegiado para el desarrollo, aunque debería ser explorado en otras disciplinas y en acciones directas de la gestión escolar. También reforzamos nuestro entendimiento de que el ocio, dado su carácter transversal, que permea varios contenidos de Educación Física, reúne cualidades para asumir la condición de tema central, como ejemplo de juegos, deportes, peleas, etc., en el ámbito de la Educación Física Escolar, apareciendo en documentos curriculares, como la Base Nacional Común Curricular , como una unidad de conocimiento, a partir de la cual se pueden desarrollar y ofrecer habilidades y contenidos a los estudiantes, con el objetivo de una educación para el ocio, a través de la educación por el ocio.
Los interesses culturales del ocio em las clases de Educación Física escolar: una propuesta de unidad didáctica para la escuela primaria
The cultural interests of leisure in school Physical Education classes: a proposal for a didatic unit for elementary school
Keywords: Educação Física escolar; Educação para o lazer; Educação pelo lazer; Interesses culturais do lazer; School Physical Education; Education for leisure; Education through leisure; Cultural interests of leisure; Educación Física escolar; Educación para el ocio; Educación por el ocio; Intereses culturales del ocio; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::EDUCACAO